2017
DOI: 10.3324/haematol.2017.178327
|View full text |Cite
|
Sign up to set email alerts
|

Clustered F8 missense mutations cause hemophilia A by combined alteration of splicing and protein biosynthesis and activity

Abstract: Dissection of pleiotropic effects of missense mutations, rarely investigated in inherited diseases, is fundamental to understanding genotype-phenotype relationships. Missense mutations might impair mRNA processing in addition to protein properties. As a model for hemophilia A, we investigated the highly prevalent F8 c.6046c>t/p.R2016W (exon 19) mutation. In expression studies exploiting lentiviral vectors, we demonstrated that the amino acid change impairs both Factor VIII (FVIII) secretion (antigen 11.0±0.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
33
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 42 publications
3
33
2
Order By: Relevance
“…This is probably a general feature of several other hematologic disorders frequently associated with mutations that are defined simply as "missense" without the interplay among several molecular mechanisms producing the disease being known. However, the results obtained by Donadon et al 1 suggest slightly milder hemophilia phenotypes than those observed in patients by clotting assays (see Table 1 in Donadon et al 1 ). It is tempting to speculate that other components could have a role in influencing the phenotype in addition to the mechanisms highlighted by Donadon et al 1 For example, studies evaluating the half life of different missense mutations are very rare and yet these are needed in order to assess the impact of clearance mechanisms on these mutant proteins.…”
contrasting
confidence: 38%
See 4 more Smart Citations
“…This is probably a general feature of several other hematologic disorders frequently associated with mutations that are defined simply as "missense" without the interplay among several molecular mechanisms producing the disease being known. However, the results obtained by Donadon et al 1 suggest slightly milder hemophilia phenotypes than those observed in patients by clotting assays (see Table 1 in Donadon et al 1 ). It is tempting to speculate that other components could have a role in influencing the phenotype in addition to the mechanisms highlighted by Donadon et al 1 For example, studies evaluating the half life of different missense mutations are very rare and yet these are needed in order to assess the impact of clearance mechanisms on these mutant proteins.…”
contrasting
confidence: 38%
“…The mutated c.6046C>T associated with the mutation was found to alter splicing and to decrease the proportion of correct transcript to approximately 75% of wild type by inducing a variable degree of skipping of exon 19. Surprisingly, they found that several other missense changes in the same exon 19 (p.G2013R, p.E2018G, and p.N2038S) are responsible for variable splicing alterations, and that only the combination of altered RNA processing and abnormal protein biology produced a clinically relevant defect (see Figure 4 in Donadon et al 1 ). This is probably a general feature of several other hematologic disorders frequently associated with mutations that are defined simply as "missense" without the interplay among several molecular mechanisms producing the disease being known.…”
mentioning
confidence: 99%
See 3 more Smart Citations